Diversifying implementation science: a global perspective - Bartels, Sophia; Haider, Shabab; Williams, Caitlin R.; Mazumder, Yameen; Ibisomi, Latifat; Alonge, Olakunle; Theobald, Sally; Bärnighausen, Till; Escallon, Juanita Vasquez; Vahedi, Mahnaz; Ramaswamy, Rohit; Sarker, Malabika (Global health, 2022)
Key Messages: As part of the greater movement to decolonize global health, leadership in implementation science needs to diversify to increase the influence of researchers and practitioners from low- and middle-income countries (LMICs) and to accelerate the development of implementation research suited to LMICs. Addressing this need will require the engagement of policy makers in LMICs to fund and shape the local research agenda, the creation of global networks to adapt or develop implementation science frameworks aligned with LMIC settings, the advancement of peer-to-peer learning and LMIC-based mentorship, and the prioritization of equity in implementation research. Achieving these aspirations will require cooperation across regions and continents to diversify global leadership in the field.
Gesehen am 18.01.2023